2003
DOI: 10.1227/01.neu.0000079485.24016.70
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Variations in Human Fetuses

Abstract: Knowledge of BP variations is important for surgeons who perform surgical procedures in the cervical and axillary regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
107
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 35 publications
12
107
0
7
Order By: Relevance
“…Although, there are abundant reports of communications between radial and ulnar nerves on the dorsal surface of the hand, and different types of these connections have been reported (Loukas et al, 2008), but connection between radial and ulnar nerves at humeral level, has not been reported greatly. In Uysal et al (2003) investigation that dissected 200 brachial plexus in human fetuses, 93 cases (46.5%) had no variations, while, variations in 53.5% of them were observed. Variations in terminal branches of the plexus are also abundant and have also been reported, for example, variations of musculocutaneous nerve were classified by Guerri-Guttenberg & Ingolotti (2009).…”
Section: Discussionmentioning
confidence: 90%
“…Although, there are abundant reports of communications between radial and ulnar nerves on the dorsal surface of the hand, and different types of these connections have been reported (Loukas et al, 2008), but connection between radial and ulnar nerves at humeral level, has not been reported greatly. In Uysal et al (2003) investigation that dissected 200 brachial plexus in human fetuses, 93 cases (46.5%) had no variations, while, variations in 53.5% of them were observed. Variations in terminal branches of the plexus are also abundant and have also been reported, for example, variations of musculocutaneous nerve were classified by Guerri-Guttenberg & Ingolotti (2009).…”
Section: Discussionmentioning
confidence: 90%
“…This type of knowledge is also very useful for neurosurgeons for treating tumors of nerve sheaths such as schwannoma, neurofibroma and non-neuronal tumors like lipoma especially in the axillary region [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of such anomalies is also important during treatment of fractures and neurotization of brachial plexus lesions [6]. Taking into consideration the commonness of occurrence of variations in the branching pattern of brachial plexus and its paramount clinical and surgical importance, the present study was undertaken in order to find the more commonly encountered anomalies as well as the rare variations of brachial plexus.…”
Section: Introductionmentioning
confidence: 99%
“…but unfortunately, the anatomical variations of brachial plexus are not rare [3,4]. More than 50% of anatomical variations in cadaveric studies of human neural system have been reported to belong to the brachial plexus [5][6][7]. The plexus supplies both motor and sensory innervations to the upper limb as well as the extrinsic thoracic muscles [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ventral rami of C5 and C6 are joined to make the superior trunk. C7 root continues and becomes the middle trunk, and the inferior trunk is shaped by the union of C8 and T1 roots [7], each of which splits into anterior and posterior divisions in the floor of the posterior triangle of the neck. At the upper border of the first rib, these divisions form cords which are related to the second part of the axillary artery.…”
Section: Introductionmentioning
confidence: 99%